Kinetics of flavour and aroma changes in thermally processed cupuaçu (Theobroma grandiflorum) pulp - SILVA, Filipa M. (2011)
Changes in `fresh' and `cooked-notes' during thermal treatment of cupuacËu (Theobroma grandi¯orum) pulp were evaluated and modelled. Isothermal experiments in the temperature range of 70±98°C were carried out and a non-linear regression was performed to all data to estimate kinetic parameters. `Fresh' and `cooked-notes' change followed simple ®rst-order (Ea=78±82kJ mol ÿ1, z =30±31°C) and reversible ®rst order (Ea=80±85kJ mol ÿ1) kinetics, respectively. Although `cookednotes' were linearly correlated with `fresh-notes' (R2=0.99), the former was a better indicator for quality degradation. These results are useful to design pasteurisation processes while minimising sensory changes.